Assessing the compatibility of the recidivist sentencing premium with retributivism in sentencing - Kourakis, Filippos (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2025)
It is a shared practice among various and diverse penal systems around the world to punish recidivists more harshly than first-time offenders. Despite the breadth of this practice, philosophically justifying this extra punishment has been a rather demanding intellectual task, especially for retributive scholars. According to the archetypical retributive scheme of punishment, the latter is justified ‘because and only because offenders deserve it’ (Moore 2009: 31). In this vein, the question which arises is whether retributivism can account for the increased punishment of recidivists, even if they engage in precisely the same criminal act with a first-time offender. The study scrutinises four retributive accounts of the recidivist premium, which seek to ground harsher punishment for recidivists by addressing the way in which culpability can be enhanced due to the offender’s prior convictions. Acknowledging each account’s conceptual limitations, this essay concludes that the most plausible retributive account for the foundation of the recidivist premium is served by the Notice theory, according to which the repeat offender is more culpable due to his/her premeditation to reoffend, albeit having experienced firsthand formal criminal punishment and thus supposedly having gotten to appreciate the implications of his/her wrongdoing.